Digital genealogy as second-wave digital humanities - Riddell, Iain E., author.
1 online resource
Keywords: In the first major engagement with Aberdeenshire's rural society since Carter's The Poor Man's Country of 1979, Riddell's study of Northeast Scotland encourages readers to consider the vast potential held by Digital Genealogy for second-wave Digital Humanities.Often overlooked in contemporary historical scholarship, this study carves out a place for Digital Genealogy in academia. Riddell constructs a new lens to examine rural society in the nineteenth century, through which he extends and challenges Carter's analysis. In recovering a breadth of people and their social networks through prosopographical data, the book reveals the agency of individuals who left minimal records. Riddell not only puts forward a fresh perspective on the social structures of Scotland's north-eastern society but also informs a discussion on the nature of Britishness both within concepts of a developed western civilisation and beyond them.This book will interest a broad readership; Scottish history enthusiasts, pursuers of Digital Genealogy and, scholars and students of the Digital Humanities will all find value in this study.